Pengaruh Faktor Internal Konsumen dan Bauran Pemasaran Terhadap Keputusan Konsumen Berbelanja Pada JM Group Palembang - Kasjim Kasjim; Zakaria Wahab (Program Studi Magister Manajemen FE Unsri, 2010)
There are many factors which are quite influence to the consumers in deciding whether or not to buy at a certain retail store, among others are: internal factors of the consumers such as culture, social class, individual characteristics, and psychological factors. In addition to those factors, decision to buy is also influenced by marketing mix which are carried out by a company, such as: products, prices, distribution channels, promotion, people, process, and physical facilities. The objective of this study is to reveal the influence of internal factors of the consumers and marketing mix on the decisions made by the consumers to buy at “JM Group” of Palembang. This study was conducted by surveying 120 respondents. The technical analysis used is multiple regression analysis.The result of the study shows that: (1) Internal factors of the consumers are significantly influence on the decisions made by the consumers to buy at “JM Group”. The magnitude of the influence of those internal factors is determined by the dimensions of cultural factor, social class, individual factors and psychological factors; (2) Marketing mix are significantly influence on the decisions made by the consumers to buy at “JM Group”. The magnitude of the influence of combined performances of marketing is determined by the dimensions of product, prices, places, promotion, people, process and physical facilities; and (3) The internal factors of the consumers and marketing mix are significantly influence on the decisions made by the consumers to buy at “JM Group”. This means that if the internal factors of the consumers change and marketing mix can be effectively implemented, the decision to buy is going to improve.Keywords: Consumer Internal Factors, Marketing Mix, Decision to buy